Multiresidue Methods Analysis to Detect Contamination of Selected Metals in Honey and Pesticides in Honey and Pollen - Mattia Casula; Francesco Corrias; Alessandro Atzei; Massimo Milia; Nicola Arru; Alberto Satta; Ignazio Floris; Michelina Pusceddu; Alberto Angioni (Foods)
Honey, a natural food with a rich history, is produced by honeybees and other species of bees from nectar, other plant fluids, and honeydew of sap-sucking insects. During foraging, these bees may be exposed to plant protection products (PPPs), metals, and metalloids, potentially leading to residues in honey and hive products that could have a negative impact on human safety. Recognizing the lack of an appropriate methodology for pesticide contamination of honey and other hive products, this research aims to support the need for studies on residues in pollen and bee products for human consumption to establish safe maximum residue levels (MRLs) for consumers. A UHPLC-MS/MS residues method and a modified QuEChERS extraction were applied to simultaneously determine 237 pesticide residues in honey and pollen. The study in North Sardinia analyzed honey and pollen samples from six areas for pesticide residues and verified 27 heavy metals and metalloid residues using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The data obtained showed residues at levels close to the LOQ of the method, cycloate in a few samples of pollen, and dichlorvos, zoxamide, cycloate, and chlorantraniliprole in honey samples. All samples showed the absence of heavy metal contamination. Overall, no risk to human health was identified. The results of this study confirm that honey and pollen may be a good bioindicator of environmental contamination of a wide area surrounding honeybee hives.